Rodzinne wzorce komunikacyjne a kompetencje językowe dzieci z niepełnosprawnością intelektualną w wizji sukcesu edukacyjnego - Chrzanowska, Iwona (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
Learning disabilities are a problem of education in each country. Still there are no effective methods to counter the phenomenon. Research results indicate that learning disabilities are a common cause of dropping out of school. B. Fatyga in her scientific research shows that are other (most important, in the teachers’ opinions) reasons, for example – negligent parenting, lack of child care. Analysis shows that it is not due to pathology in the family, the poor economic situation of the family or a low level of education of the parents. It is possible that the cause of difficulties in learning (in some of the children) are dysfunctional communication patterns learned from the family environment.
Keywords: rodzina; komunikacja; kompetencje językowe; dzieci; niepełnosprawni; edukacja